The Role of E-Commerce Tax on Indonesian State Revenue During the Covid-19 Pandemic in Islamic Economic Perspective - Ria Atika; Tulus Suryanto (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2022)
The Covid-19 pandemic is changing economic trends at this time. E-commerce grew rapidly in recent years and has become more intense due to the Covid-19 pandemic. E-Commerce Tax provides solutions in the midst of the Covid-19 pandemic. The purpose of this writing is to illustrate the role of the E-commerce Tax on Indonesia's State Revenue during the Covid-19 pandemic in an Islamic Economic Perspective. The method used is descriptive qualitative research with secondary data sources and documentation data collection methods. Based on an analysis of data obtained from journals, books, and the internet in the form of company records or documentation, government documentation or government publications, industry analysis by media, websites and others, it was found that E-commerce Tax has a role in Indonesia's state revenues by increasing state tax revenues during the Covid-19 pandemic. In the Islamic Economic Perspective the tax set in e-commerce is in accordance with Islamic teachings, because it is set on the basis of achieving justice between conventional business actors and also online business actors.